Recent developments of acupuncture in Australia and the way forward - Zhang Claire; Yang Angela; Zhang Anthony; Xue Charlie; Story David (BMC, 2009)
Abstract Almost one in ten Australians has received acupuncture treatment by acupuncturists and/or medical doctors in private clinics. The majority of Australian health insurance funds offer rebates for acupuncture. Statutory regulations for acupuncture have been implemented in the State of Victoria, Australia. Six acupuncture degree courses have been approved by the Chinese Medicine Registration Board of Victoria and/or accredited by the Australian Acupuncture and Chinese Medicine Association. Furthermore, a number of clinical trials of acupuncture on allergic rhinitis, pain and women's health were carried out in Australia. Recent developments of acupuncture in Australia indicate that through adequate and appropriate evaluation, acupuncture begins to integrate into mainstream health care in Australia.